The impedance spectroscopy studies of PVC / ENR 50 / LiCF 3so3 and PMMA / ENR 50 / LiCF3so3 electrolytes - Aziz, M.; Latif, F.; Chew, C. L.; Katun, N. (Scitec Publications Ltd., 2006)
Free standing solid polymer electrolyte films based on poly (methyl methacrylate) PMMA and Poly (vinyl chloride), PVC can be obtained when blend with 10% and 50% of 50% epoxidised natural rubber, ENR 50 respectively. This work conducted impedance spectroscopy studies on PVC / ENR 50 and PMMA / ENR 50 based electrolyte systems when doped with lithium triflate, LiCF 3SO3 salt. PVC / ENR 50 / LiCF3SO3 exhibited higher bulk resistance, Rb and lower conductivity values than PMMA / ENR 50 based electrolytes. The highest conductivity achieved for PMMA / ENR 50 blend is 5.09 Ã— 10-5 S/cm and 3.64 Ã— 10-8 S/cm for PVC / ENR 50 blend when doped with 60% of LiCF3SO3 salt. The plots of logarithm of ionic conductivity against the reciprocal of absolute temperature revealed that the ionic conduction in PVC / ENR 50 / LiCF3SO3 electrolyte follows the WLF theory and PMMA / ENR 50 / LiCF3SO3 electrolyte obeyed the Arrhenius behavior.